Persistent, Bioaccumulative, and Toxic Chemicals in Wild Alpine Insects: A Methodological Case Study. (21st March 2022) - Hierlmeier, Veronika Rosa; Struck, Nils; Krapf, Patrick; Kopf, Timotheus; Hofinger, Anna Malena; Leitner, Viktoria; Stromberger, Philipp Jakob Ernest; Freier, Korbinian Peter; Steiner, Florian Michael; Schlick‐Steiner, Birgit Christiane
Abstract: With their high persistence in the environment and their potential for long‐range atmospheric transport, persistent, bioaccumulative, and toxic chemicals (PBTs) may be among the numerous anthropogenic threats to insect populations worldwide. The effects of PBTs on insects have been investigated in the laboratory, but topical field studies are scarce. A reason might be the multiple challenges faced by PBT‐related field studies on wild insects. We studied two species of bumblebees ( Bombus spp.) and of ants ( Formica spp.) in two high‐elevation locations in the Austrian and German Alps to tackle two of these challenges. First, PBTs occur in minuscule concentrations compared with other substances in the environment. Therefore, the practicability of body burden data from pooled individuals was tested. Second, fitness proxies like fecundity, which typically are endpoints for chemical toxicity, are difficult to quantify in the field. Hence, fluctuating asymmetry of bumblebee wings and ant heads was tested as an alternative endpoint. To exclude the possibility that fluctuating asymmetry was caused by genetic stressors, inbreeding levels were estimated using population‐genetic markers, and their relationships to fluctuating asymmetry in the same individuals were assessed. We successfully quantified polychlorinated biphenyls and Hg as PBTs using the pooled samples and found PBT data from pooled individuals useful, in that significant correlations to fluctuating asymmetry were identified in bumblebees and ants. This finding confirmed the potential of fluctuating asymmetry to indicate PBT effects in wild insects. Inbreeding did not interfere with PBT links to fluctuating asymmetry in any instance. Our findings contribute to the development of a quantitative methodological framework for investigating the effects of persistent environmental chemicals on wild insects.  Environ Toxicol Chem 2022;41:1215–1227. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : The bioaccumulation of persistent, bioaccumulative, and toxic chemicals in wild alpine insects was proved via chemical analysis. The data showed some significant correlations with measured asymmetries of the body structures of the insects. Inbreeding, analyzed with genetic markers, did not interfere with these links.